If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30x + -6 = 33x Reorder the terms: -6 + 30x = 33x Solving -6 + 30x = 33x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33x' to each side of the equation. -6 + 30x + -33x = 33x + -33x Combine like terms: 30x + -33x = -3x -6 + -3x = 33x + -33x Combine like terms: 33x + -33x = 0 -6 + -3x = 0 Add '6' to each side of the equation. -6 + 6 + -3x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -3x = 0 + 6 -3x = 0 + 6 Combine like terms: 0 + 6 = 6 -3x = 6 Divide each side by '-3'. x = -2 Simplifying x = -2
| 60x^2+240x=0 | | 2xy/3xy | | 11x=3x+12 | | 8(x+1)=2(x+3) | | 16/5=-8y | | 3x+6=8X+4 | | 9x+8=11x+8 | | 6x+7+2x+5=15 | | .5d-3d+5= | | 4(8x)=176 | | 5m^2-m-3=0 | | 4(3t+-2)=32 | | logx=3.2 | | 43j^2+11j=0 | | 23=x+6 | | u^2+30u=0 | | 5x-1=-3+-9 | | f(x+3)=4x+7 | | -6(5x+2)=-48 | | (3x-2)(x+5)=5 | | 2n=45 | | 9x-10=3x+25 | | 3s^2+13s-10=0 | | 2(13+x)=41x | | 18=-6/7y | | 8x+9=10x-1 | | 2+7+x=18 | | 4x-6+2x-2=-20 | | 4x-6+2x-2=-20I | | -19(15x+17)= | | 1x(4x-20)=180 | | 4g^2+43g-11=0 |